Cross-sectional assessment of the ellipsoid zone and the retinal pigment epithelium-Bruch membrane complex after systemic isotretinotin use - Genç Işık, İrem; Işık, Mehmed Uğur (Informa UK Limited, 2022)
To evaluate the cross-sectional areas of the retinal pigment epithelium-Bruch membrane complex (RPE-B) and ellipsoid zon (EZ) and the thickness of the macula, retinal nerve fibre layer (RNFL), and ganglion cell-inner plexiform layer (GC-IPL) in patients using short-term systemic isotretinoin.A total of 43 right eyes of 43 patients treated with systemic isotretinoin for acne vulgaris were included in this prospective study. Macula, GC-IPL, RNFL thicknesses and central cross-sectional EZ and RPE-B areas were evaluated with optical coherence tomography (Zeiss, Cirrus HD OCT 5000) prior to treatment and in first, second and third months after the onset of isotretinoin treatment. For the measurement of EZ and RPE-B area, foveal EDI-OCT scans were binarized by using the public domain software ImageJ 1.51 s.Mean duration of isotretinoin treatment was 77 ± 15 days and mean dose was 2228 ± 574 milligrams. There was a statistically significant increment in central cross-sectional EZ and RPE-B areas in each follow-up examination, when analysed by repeated measurement analysis (p:0.002 and p:0.006, respectively). There was no correlation between total isotretinoin dose and the difference between final and basal EZ and RPE-B areas (p > 0.05, for both). When repeated measurements in follow-up examinations were compared, GC-IPL thicknesses except the superotemporal region (p:0.040) and RNFL thicknesses did not show a significant difference (p > 0.05). There was not any significant relation between total isotretinoin dose and 3rd month and basal measurement differences in macula, GC-IPL and RNFL thicknesses in any area (p > 0.05, for all).There has been an increase in the area of RPE-B and EZ with short-term use of isotretinoin therapy. Future studies examining the relationship between functional tests and the RPE-B and EZ areas may provide more in-depth information on the effects of isotretinoin in the eye.
Keywords: Visual Acuity; Humans; Bruch Membrane; Prospective Studies; Retinal Pigment Epithelium; Isotretinoin; Tomography, Optical Coherence